Foregrounding historical consciousness as a critical resource for emancipatory potential from a gendered identity : a case of reinventing the self from marginality in Christine Hagion’s selected poems - Mkhatshwa, Elijah (African renaissance, 2018)
This article examines how questioning the naive model of the social construction of the 'Other' and the Self as 'unique, single and unchanging' enlightens any would-be reader of the awakening of consciousness for the possibility of forging "new subject positions". Such newly acquired subjections are depicted as affording the individual a distinctive voice with authority to reinvent himself or herself from marginality in relation to significant 'Others'. Thus, in this article historical consciousness is central as it is construed as having an emancipatory potential since it captures the motivations of those who are deemed 'other' the compulsive urge to speak. In definitional terms, this article advocates the view that historical consciousness is the ability to recognize the epochal quality of an event that is happening now, to see the event with the eyes of future generations (Arnold Gehlen). It is against this background, therefore, that in this article the question of voice and agency are central as the protagonist is presented as a representative of a vast constituency of those women who are suffering the same plight. So, the foregrounding of historical reminiscence is used as a strategy that the protagonist uses to draw invaluable insights from her lived experience of having lost her identity or individuality which renders her conscious of the fluidity of identity. Notably, therefore, the poems speak to the condition of those who are subjected to abusive relationships and thus seek not only to rediscover their selves but also to reclaim or regain their lost identities and freedom.